Tools, Techniques and Protocols for Monitoring Environmental Contaminants - Kaur Brar, Satinder; Kaur Brar, Satinder; Hegde, Krishnamoorthy; Pachapur, Vinayak Laxman (Elsevier Science, 2019)
Tools, Techniques and Protocols for Monitoring Environmental Contaminants describes information on the strategic integration of available monitoring methods with molecular techniques, with a focus on omics (DNA, RNA and protein based) and molecular imprinted polymer and nanomaterial based advanced biosensors for environmental applications. It discusses the most commonly practiced analytic techniques, such as HPLC, MS, GCMS and traditional biosensors, giving an overview of the benefits of advanced biosensors over commonly practiced methods in the rapid and reliable assessment of environmental contaminants. As environmental contaminants have become one of the serious concerns in terms of their rapid growth and monitoring in the environment, which is often limited due to costly and laborious methods, this book provides a comprehensive update on their removal, the challenges they create for environmental regulatory agencies, and their diverse effects on terrestrial and aquatic environments. - Provides methods for assessing and monitoring environmental contaminants - Includes recent advancement in molecular techniques - Outlines rapid environmental monitoring methods - Explains the use of biosensors for environmental monitoring - Reviews monitoring methods beyond conventional analytic techniques